A comparison of the level of fear of death among students and nursing professionals in Mexico - Edna Johana Mondragón-Sánchez; Erika Alejandra Torre Cordero; María de Lourdes Morales Espinoza; Erick Alberto Landeros-Olvera (Universidade de São Paulo, 2015)
OBJECTIVE: to compare the level of fear of death in nursing students and professionals. METHOD: this was a comparative-transversal study examining 643 nursing students and professionals from a third-level institution. A random sampling method was employed, and the sample size was calculated by power analysis. The study was developed during three stages: the first stage consisted of the application of a pilot test, the second stage involved the recruitment of the participants, and the third stage measured the participants' responses on the Collett-Lester Fear of Death Scale. RESULTS: the average fear of death was moderate-high (-X=3.19±0.55), and the highest score was observed for the fear of the death of others (-X=3.52±0.20). Significant differences in the perceptions of fear of death were observed among the students of the first three years (p<.05). However, no significant differences were observed among the first- and fourth-year students and professionals (p>.05). CONCLUSIONS: it is possible that first-year students exhibit a reduced fear of death because they have not had the experience of hospital practice. Students in their second and third year may have a greater fear of death because they have cared for terminal patients. However, it appears that greater confidence is acquired over time, and thus fourth-year students and professionals exhibit less fear of death than second- and third-year students (p<.05).